ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN AWAL (Studi pada perusahaan IPO yang Listing di Bursa Efek Indonesia periode 2006-2012) - Desty Deriyani, 09.05.52.0081 (Students Journal of Accounting and Banking, 2013)
Go public company sold shares first in the primary market before trading in the secondary market (the stock exchange). Price of the shares sold in the primary market is determined by agreement between the underwriter to the issuer, while the stock price in the secondary market is determined by the market mechanism. This study intends to determine the factors that affect IPO initial return, by testing whether the scale of the company, EPS, Profitability, Leverage Levels, Age Company, Old Shareholder Ownership Proportion, Auditor Reputation, Reputation Underwriter, and PER significantly affect return initial stock.This study uses secondary data from 60 companies that IPO on the Stock Exchange in the period 2006 to 2012 were collected by purposive sampling method. The dependent variable in this study is the early return of the stock, while the independent variable is the amount of the company, EPS, Profitability, Leverage Levels, Age Company, Old Shareholder Ownership Proportion, Auditor Reputation, Reputation Underwriter, and PER. They were tested using multiple linear regression analysis. The test results found evidence that only the variable degree of leverage positive influence on early returns. Underwriter reputation negatively affect initial returns. Price Earning Ratio variables negatively affect initial returns. Variable scale company, earnings per share, return on assets, firm age and no significant positive effect on initial returns. Variables and auditor reputation underwriter reputation negatively affect early return.Keywords: IPO, initial returns, the amount of the company, EPS, Profitability, Leverage Levels, Age Company, Old Shareholder Ownership Proportion, Auditor Reputation, Reputation Underwriter, and PER